Cloud Computing for Voxel-Wise SEM Analysis of MRI Data. Issue 3 (4th May 2019) - Pritikin, Joshua N.; Schmitt, J. Eric; Neale, Michael C.
Abstract : As data collection costs fall and vast quantities of data are collected, data analysis time can become a bottleneck. For massively parallel analyses, cloud computing offers the short-term rental of ample processing power. Recent software innovations have reduced the effort needed to take advantage of cloud computing. To demonstrate, we replicate a voxel-wise examination of the genetic contributions to cortical development by age using evidence from 1748 MRI scans. Specifically, we employ off-the-shelf Kubernetes software that permits us to re-run our analyses using almost the same computer code as was published in the original article. Large, well funded institutions may continue to maintain their own computing clusters. However, the modest cost of renting and ease of utilizing cloud computing services makes unprecedented compute power available to all researchers, whether or not affiliated with a research institution. We expect this to spur innovation in the sophisticated modeling of large datasets.